Pengaruh Metode Siglar (Simulasi Gigitan Ular) Terhadap Keterampilan Penanganan Gigitan Ular Pada Petani Di Desa Lobener Lor Kabupaten Indramayu - Hery Prayitno; Leny Nur Alifah (STIKES Ngesti Waluyo, 2026)
Indonesia has a high risk of snakebites, especially in lowland areas and agricultural lands, which are the main habitats of various snake species. Snakebites often occur among agricultural workers due to a lack of preventive measures. Snakebite cases have increased from year to year and have resulted in death. Snakebites are an emergency condition that can cause death if not treated quickly and appropriately. In Lobener Lor Village in Indramayu Regency, there was a case of death due to snakebites that did not receive appropriate first aid. This study aims to determine the effect of the SIGLAR (Snake-Bite Simulation) method on snakebite-handling skills among farmers in Lobener Lor Village. This type of research is quantitative with a quasi-experimental design with a one-group pretest-posttest approach. The sampling technique used was purposive sampling, and the sample comprised 30 farmers. The instruments used were observation checklist sheets for snakebite handling skills and standard operating procedures (SOPs). The bivariate data analysis used was the Wilcoxon Signed-Rank Test. The results of the study showed that the median score of skill increased from 3.00 before the intervention to 8.00 after the intervention, and that there was a significant difference in skills before and after the SIGLAR method was administered (p < 0.05). Simulation proved effective in improving farmers' skills in providing first aid for snake bites.